The Functions of English Terms in Korean Popular Music (K-Pop): A Register Analysis - Asfi Aniuranti (Surakarta English and Literature Journal, 2020)
This study is a part of register research aimed at investigating the functions of English terms in Korean Popular Music (K-Pop). There are many English terms used in K-Pop, and those terms are assumed to have some purposes. The researcher completed this study through several phases called data gathering, data analysis, and data presentation. The present study reveals that there are at least eleven functions of English terms in K-Pop. The terms are utilized for promoting the singers’ music projects, showing self as something different from the others, communicating briefly, praising the singers’ physical appearances, appreciating the singers’ achievements, giving comment on the singers’ attitudes, commenting on the singers’ fashions, joking, giving appreciation to the music agencies, appreciating the fans, and showing hatred toward the singers.